FR1.3: Gender-responsive investments and policies in response to the crisis brought about by Russia's war on Ukraine - Ringler, Claudia; Bryan, Elizabeth (International Food Policy Research Institute, 2022)
Following on the heels of the COVID-19 pandemic, the global food crisis resulting from Russia's war on Ukraine is exacerbating existing challenges in many low-income countries, including rising food, fuel, and fertilizer costs. These price shocks threaten food security, access to healthy diets, and people's ability to rebound from multiple crises, including rebuilding savings and assets that were depleted to cope with the protracted COVID-19 pandemic. Evidence suggests that the impacts of these compounding crises are likely to have differential effects on men and women. To reduce the gender gap in resources to confront these crises and the resulting welfare outcomes will require pro-active, gender-responsive approaches. Previous research shows that women are more likely to experience food insecurity following food price shocks, as reflected by their reducing diversity of diets, or abstaining from food consumption to make more food available to others in the family. Women also face greater challenges accessing agricultural inputs and resources—higher fertilizer and energy input prices can further constrain women's access to inputs, exacerbating the gender productivity gap. At the same time, changes in production practices due to rising input costs may add to women's already high labor and time burden, for example, when agro-chemicals are replaced by weeding or motorized irrigation is replaced by manual water lifting. This study is using data from phone surveys on the impacts of the Ukraine crisis as well as evidence from other recent food price crisis and a roundtable to identify key gender impacts and measures that can reduce adverse gendered impacts.